CSR inflections: an overview on CSR global strategies adopted by companies in Malaysia and Other Asian countries - Naila Aaijaz; Mohamed Dahlan Ibrahim (IBIMA Publishing, 2012)
Since the early 2000s, the conversation on CSR in Malaysia has been moving ahead rapidly. Whereas commentators tended to understand CSR in the 1990s as exclusively dealing with supplying chain issues, the last few years have seen changing expectations on company performance when it comes to social and environmental issues. In this paper, the researchers have tried to focus on a handful of key changes in the way various groups perceive good company practices, and outline some of the key challenges and opportunities in the CSR area. In a developing and progressive country like Malaysia, CSR stands to be of vital importance for a mutual and symbiotic growth. The growth defined is not only for the individual but for the society as a whole and country at large.